An overview application of silver nanoparticles in inhibition of herpes simplex virus. (17th February 2018) - Akbarzadeh, Abolfazl; Kafshdooz, Leila; Razban, Zohre; Dastranj Tbrizi, Ali; Rasoulpour, Shadi; Khalilov, Rovshan; Kavetskyy, Taras; Saghfi, Siamak; Nasibova, Aygun N.; Kaamyabi, Sharif; Kafshdooz, Taiebeh
Abstract: Nanoscale particles and molecules are a potential different for the treatment of disease because they have distinctive biologic property based on their structure and size, which is different from traditional small-molecule drugs. The antimicrobial mechanisms of silver nanoparticles include the formation of free radicals damaging the bacterial membranes, interactions with DNA, adhesion to cell surface altering the membrane properties, and enzyme damage. In this review, we focus on applications of silver nanoparticles in inhibition of herpes simplex virus.